2010
DOI: 10.4104/pcrj.2010.00015
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the major studies in COPD: problems and pitfalls in translating research evidence into practice

Abstract: SummaryTranslating the growing evidence base on COPD management into practice can be challenging and understanding the strengths and weakness of published studies is crucial. Studies should conform to the standards of CONSORT statement; they should be sufficiently powered, participants should be randomised, there should be assignment concealment, and the outcome measures and analyses should be decided in advance.The interpretation of the results may be affected by age and severity inclusion criteria for the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Study populations for most pharmacological and non-pharmacological trials of patients with COPD are often not representative of patients with COPD [4,5,37,38]. In pharmacological trials patients are often excluded because of co-morbid conditions or current medication use [34].…”
Section: Discussionmentioning
confidence: 99%
“…Study populations for most pharmacological and non-pharmacological trials of patients with COPD are often not representative of patients with COPD [4,5,37,38]. In pharmacological trials patients are often excluded because of co-morbid conditions or current medication use [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, RCTs are conducted in controlled settings and historically have not included populations that are generally representative of real-world populations. Importantly, older individuals are frequently excluded from COPD RCTs, as are individuals with asthma and many other comorbidities [28]. While there is RCT-based evidence for LAMA effectiveness in reducing exacerbation-associated hospitalization risk, LAMA effectiveness at reducing the risk of readmission or mortality after a COPD-related hospitalization in a real-world population has not been well studied.…”
Section: Key Pointsmentioning
confidence: 99%
“…In a recent Scottish study, the median time from the earliest reported symptom to consultation was 99 days, 8 and a questionnaire revealed that 75% of participants had unrecognised symptoms of lung cancer. The presence of COPD, which increases the risk of lung cancer up to five times, 9 often delays diagnosis. Estimates suggest that the causes for delay between first symptom and presentation to specialist care can be split equally between patient-related and primary care-related issues.…”
Section: Editorialsmentioning
confidence: 99%
“…A recent study suggests that a median of only 6% (range 0% -43%) of patients treated for asthma meet the eligibility criteria for major trials cited in evidencebased treatment guidelines. 8 In his excellent article published in the PCRJ in 2010, 9 Halpin outlines many fundamental limitations of landmark COPD trials and how such trial data may be difficult to apply at the primary care level. For example, in relation to trials such as ISOLDE, 10,11 TORCH 12 and UPLIFT, 13 there has been minimal, if any, discussion around the pragmatic implications of high early withdrawal rates from the active treatment arms in these studies -a reality that invariably compounds the difficulty of translating trial information into the most cost-effective care for our primary care patients.…”
mentioning
confidence: 99%